Silent hero. The metaphorical role of the ruins of Warsaw in Polish fiction films from 1949 to 1960 - Giza, Barbara (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article is an analysis of the image of ruins of Warsaw in Polish feature films after World War II. There is a strong tendency to connect this image with the current political (and psychological) situation, from the enthusiasm of rebuilding Warsaw just after the war to the depressive moods of the late fifties and sixties. The ruins of the city are depicted as a symbol of political and social changes in Poland in this article.